Annual report 2011 - (:unkn) unknown (Publications Office of the European Union, 2012)
The annual report 2011 gives an overview about Cedefop's performance in 2011 according to different indicators It reflects the medium-term priorities for the period 2012-14. These priorities are designed to support the new policy framework set by Europe 2020. Furthermore, the report describes key achievements in the following five areas: Informing European vocational education and training policies; Interpreting European trends in and challenges for skills, competences and learning; Assessing vocational education and training's benefits; Raising the profile of vocational education and training; Management, resources and internal controls. A further chapter analyses the implementation of the 2011 work programme by medium-term priorities, activities and projects. (Hrsg., BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; I 1.5 Internationale Organisationen & Institutionen; I 2.2 Europa; CEDEFOP; Berufsbildungsforschung; EU-Bildungspolitik; Europäische Union; 2011